An interactive WebGIS observatory platform for enhanced support of integrated coastal management - Oliveira, A.
A new WebGIS observatory platform is presented, tailored for risk assessment and emergency preparation and response in coastal areas. The tool combines a sophisticated forecast modeling system for multi-scale analysis of water bodies, including waves, hydrodynamics and oil spills prediction, with real-time monitoring networks for forcing and continuous validation purposes. Tailor-made visualization and analysis products, conceptualized for multiple uses through a service-oriented framework, provide an easy and interactive access to both data and predictions. The system was customized for oil spills risk assessment and the rapid response to an oil spill emergency, and applied to the Aveiro lagoon. The tool addresses oil spill problems in two complementary ways: 1) a detailed risk assessment through georeferenced hazard and vulnerability maps and GIS layers of information to support the definition of contingency plans; and 2) the visualization of georeferenced oil spill predictions produced by a real-time oil spill forecasting system. Improvements relative to existing risk systems are 1) the possibility of selecting quick-access predictions for fast emergency response or high-quality, georeferenced GIS prediction products, 2) the flexibility in accessing products to evaluate local impacts of oil spills both in the water column and in the intertidal areas, and 3) the enhanced hazard and risk analysis through a combination of a multi-scenarios approach with the historical database of spill predictions, forced by daily hydrodynamic forecasts. Dependability of information, for both model results and monitoring data, is being implemented through innovative ways, targeting the robustness and quality control of the WebGIS platform.